Additive Manufacturing Methods for Producing Hydroxyapatite and Hydroxyapatite-Based Composite Scaffolds: A Review - Kumar, Anuj; Kargozar, Saeid; Baino, Francesco; Han, Sung Soo (Frontiers in Materials, 2019)
Hydroxyapatite (HAp) has been considered for decades an ideal biomaterial for bone repair due to its compositional and crystallographic similarity to bio-apatites in hard tissues. However, fabrication of porous HAp acting as a template (scaffold) for supporting bone regeneration and growth has been a challenge to biomaterials scientists. The introduction of additive manufacturing technologies, which provide the advantages of a relatively fast, precise, controllable and potentially scalable fabrication process, has opened new horizons in the field of bioceramic scaffolds. This review focuses on 3D-printed HAp scaffolds and related composite systems, where the calcium phosphate phase is combined with other ceramics or polymers improving the mechanical properties and/or imparting special extra-functionalities. The main applications of 3D-printed HAp scaffolds in bone tissue engineering are presented and discussed; furthermore, this review also emphasizes the most recent achievements towards the development and testing of multifunctional HAp-based systems combining multiple properties for advanced therapy (e.g. bone regeneration, antibacterial effect, angiogenesis and cancer treatment).